Oneiric Motifs in the Poetics of Venedikt Erofeev - Natalya Gonchar-Khanjyan, Natalie; Karapetyan, Inga (Bulletin of Yerevan University H: Russian Philology, 2024)
The theme of sleep and dreams has intrigued minds and souls from ancient times; today, it has become especially relevant and has become the object of study of various disciplines (philosophy, anthropology, cultural studies, psychology). Throughout the history of the world literature, oneiric and dreamlike motifs and techniques expanding the author’s capabilities in ideological and artistic mastering of reality and creativity marked works of many authors. This has repeatedly and variously affected, in particular, the works of such classics of Russian prose as Dostoevsky, Turgenev, Tolstoy, followed by Zamyatin with his novel «We», Bulgakov with the novel «The Master and Margarita», as well as others, up to representatives of the latest literature – first of all Venedikt Yerofeyev, and then a number of postmodern prose writers – Viktor Pelevin, Yuri Mamleev, Dm.Liksperov, V. Sorokin and others, who chose sleep as one of the basic elements of their poetics. The purpose of this article is to trace as a cross-cutting plot and compositional line oneiric motifs and techniques in the cult poem «Moscow-Petushki» by Venedikt Yerofeyev – the forerunner of Russian postmodernism, whose work has been in the focus of attention in recent decades. With the outline of the literary background and the emphasis on socio-culturally determined features of the latest Russian prose, the article attempts to connect interdisciplinary research, in particular, a number of provisions of psychology, based on the oneiric cross-cultural myth, by revealing intertextual connections, parallels, to give their interpretation to the dream literary text of modernity.